Kultura fizyczna łodzian na przełomie XIX i XX wieku - Piestrzeniewicz, Marta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
A lot of factors influenced the development of physical culture in Lodz in the 19th century, for example the invader’s policy, industrial development of the town, financial conditions, social and nationalistic position as well as Lodz intellectuals’ activity. The influence of European way of physical education was also of importance. Germans popularized in Lodz different sports and active forms of spending free time and in that way introduced German customs in Poland. At that time the most popular sport activities were: game shooting, horsemanship, cycling, football, tennis and gymnastics. The greater part of associations and institutions, which came into existence in Lodz of those days, presented closely nationalistic character. Up to 1886 only one sport club, that came into being in 1824, existed in Lodz. That was Lodz Shooting Society and only Germans belonged to it. The beginning of the birth of Polish sport should have been associated with the creation of the first Polish sport club in 1889, called Lodz Cyclist Association of The Warsaw Consulate. Polish lovers of cycling belonged to that sport club. Sport was of great importance as far as the life of Lodz society was concerned. It contributed to the reduction of the social pathology, trained the character of the people as well as schooled to surmount the exterior difficulties. Those factors were very essential for people who must have functioned in under the oppression of the invader. Sport education contributed a rich heritage of values to the Lodz society.